Look Both Ways: Help Protect Your Family on the Internet - Linda Criddle (Prentice Hall of India Private Limited, 2007)
Your parents taught you to look both ways before crossing the street. Now, learn the rules of the road-and help protect yourself online with Internet child-safety authority Linda Criddle. Using real-life examples, Linda teaches the simple steps you and your family can take to help identify and avoid Internet dangers-and still enjoy your time online. Help protect your family and learn how to: Blog, instant message, and play games without inadvertently revealing personal information Take safety precautions if you participate in online dating Recognize and avoid phony e-mail, instant messages, and Web sites Project an attitude online that can help detract potential predators Talk about safe Internet practices with your family Report abuses and suspicious activities to the proper authorities